Implementasi Kebijakan Pencegahan dan Penanganan Kekerasan Seksual di Kampus Islami Universitas Muhammadiyah Jakarta - Debi Primanda; Izzatussolekha Izzatussolekha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The goal of this research is to find out how the policy for preventing and handling sexual violence is implemented for students on UMJ campus. The theory used is from of T.B. Smith which consists of several indicators, namely a) Idealized Policy; b) Target Group; c) Implementing Organization; and d) Environmental Factors. This research uses qualitative research methods with a descriptive approach. Data obtained by observation, interviews and documentation. The results of this research show that: 1) Idealized Policy, Muhammadiyah University Jakarta has derivative regulations, but they have not been massively informed; 2) Target Groups, namely this regulation is intended for students, but its implementation is not yet optimal; 3) Implementing Organization, UMJ has a PPKS institution which has a program concept, but students as a whole are not yet aware of the existence of this institution; 4) Environmental Factors, Permendikbudristek No. 30 of 2021 cannot be said to be completely in line with the Islamic campus cultural environment because the regulation contains the phrase 'without the victim's consent' which is biased in meaning. Apart from that, the shift in Islamic culture at UMJ was also caused by many factors, such as social, economic and political factors involving power relations.